Removal of Oil Waste by iron oxide Biochar Prepared from Sugarcane Bagasse - Pushpa, Pushpa latha A/P Subramaniam (Progress in Engineering Application and Technology, 2021)
Nowadays, the dissolution of microsized oil droplets from water is strongly required by the environmental protection. Oil pollution has become a severe environmental issue and has attracted global concern. However, the oil released from household activities particularly cooking and bathing, could contaminate the surrounding environment and human health. The presence of contaminants in oil waste raises concerns as small quantities of organic chemicals have been shown to be carcinogenic to mammals and can pose a risk to both human health and aquatic organisms. Therefore, the presents study investigated the performance of iron oxide sugarcane bagasse biochar in the removal of oil waste from aqueous solution. The iron oxide sugarcane bagasse biochar is produced using co-precipitation method of iron chloride (FeCl3) and iron sulphate (FeSO4). Then, the magnetic biochar is characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). The efficiency of the magnetic biochar in removing oil waste are measured by performed a batch experiment with different iron oxide biochar dosages, oil waste concentration and contact time. At the end of the experiment, the iron oxide sugarcane bagasse biochar is separated by using a magnet. The optimum performance condition of the iron oxide sugarcane biochar is then undergone three cycles of adsorption process to determine the adsorption capacity. From the results of the adsorption experiment, the optimum separation of oil waste was achieved when contact with 0.25% concentration of oil,1.5g of magnetic sugarcane bagasse biochar at 120 seconds with separation efficiency of 99%. After performed three cycle of adsorption process, the iron oxide biochar still showing an excellence removing performance which towards zero waste production could be achieved. The findings constitute that the iron oxide sugarcane bagasse biochar is efficient to be used in removal of waste cooking oil from aqueous solution. Thus, the prospect of iron oxide biochar utilization is promising as it is can customized for specific environmental applications.